2019
DOI: 10.3390/biom10010036
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Soluble Polysaccharides in Tannin-Cell Wall Interactions in Model Solutions and in Wines

Abstract: The interactions between tannins and soluble and insoluble cell wall components are, in part, responsible for the low quantities of tannins found in wines compared with the quantities in grapes. The use of polysaccharides to compete with cell wall components could be an interesting approach for improving the chromatic and sensory characteristics of wines. The effect of two commercial polysaccharides, pectin and mannan, on limiting tannin-cell wall interactions was studied in a model solution, measuring the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
(78 reference statements)
0
10
1
Order By: Relevance
“…The decrease in chromatic parameters in the wine treated by electrodialysis could be due to the adsorption of high molecular weight compounds in the membranes, as described by Bdiri et al [43]. Some of these compounds, such as polysaccharide polymers, prevent tannin aggregation and precipitation and their elimination could facilitate a decrease in color intensity [44,45]. However, contrary to our findings, other authors have reported that electrodialysis does not affect wine color [42].…”
Section: Chromatic and Phenolic Parameterscontrasting
confidence: 62%
“…The decrease in chromatic parameters in the wine treated by electrodialysis could be due to the adsorption of high molecular weight compounds in the membranes, as described by Bdiri et al [43]. Some of these compounds, such as polysaccharide polymers, prevent tannin aggregation and precipitation and their elimination could facilitate a decrease in color intensity [44,45]. However, contrary to our findings, other authors have reported that electrodialysis does not affect wine color [42].…”
Section: Chromatic and Phenolic Parameterscontrasting
confidence: 62%
“…It is well known that PAs may be bound by the CWM via hydrogen bonds and hydrophobic interactions [130]; between the CWM constituents, proteins showed the highest binding capacity [126,131]. Considering the polysaccharides, pectins showed higher affinity for PAs than hemicellulose [132,133] while weak interactions were found with cellulose [134].…”
Section: Interactions Between the Cwm And Pasmentioning
confidence: 99%
“…9,[11][12][13] In blackberry fruits, polyphenols are the main compounds responsible for fruit sensory properties, and their stability is highly dependent on factors such as light exposure, pH, native chemical structure, sugar conjugation, temperature, metal ions, oxygen, and enzymes. 14,15 Phenolic compounds are stored in cell structures (e.g. vacuoles and cell walls) of the skin, pulp and seeds of fruits.…”
Section: Introductionmentioning
confidence: 99%
“…vacuoles and cell walls) of the skin, pulp and seeds of fruits. 15 These compounds are bound to macromolecules, such as proteins and peptides (linking the phenolic group of the phenol ring with the -NH group of peptides) or carbohydrates (liked by αand β-glycosidic bonds), the dry matter content of which is about 80% and 5%, respectively. 8,16 It should be noted, however, that these macromolecules undergo marked degradation during GID, becoming bioavailable sugars and small peptides/amino acids.…”
Section: Introductionmentioning
confidence: 99%